Complementary resource use in intercropped faba bean and cabbage by increased root growth and nitrogen use in organic production. (31st October 2021) - Shanmugam, Sindhuja; Hefner, Margita; Pelck, Jeanett S.; Labouriau, Rodrigo; Kristensen, Hanne L.
Abstract: Intercropping can improve yield and nitrogen use efficiency in organic vegetable production by pairing crops with complementary resource use. An intercrop field experiment was conducted to determine yield, root growth and nitrogen (N) dynamics using faba bean ( Vicia faba L.) grown as a vegetable and pointed cabbage ( Brassica oleracea var. capitata cv. conica). Both crops were grown in monocropping (MC) and intercropping systems (IC). Minirhizotrons were used to measure root growth. Yield of pointed cabbage per metre row was 28% higher under the IC system than under MC, whereas faba bean yield as fresh seeds did not differ. The land equivalent ratio was 1.06, showing that improved yield under IC resulted from efficient land resource use. Even though MC cabbage had the highest aboveground biomass, total N accumulation was higher under IC and MC faba bean systems. Both root frequency and intensity were greater under IC faba bean rows compared with MC faba bean because of the presence of cabbage roots in faba bean rows. Monocropped cabbage had the highest root intensity and the lowest amount of soil mineral N in the 0–1.5 m depth after harvest. Monocropped cabbage was efficient in assimilating N, whereas MC faba bean was efficient in exporting N as harvestable yield. The nitrogen use efficiency using the IC system (75%) was higher than growing faba bean (44%) and cabbage (65%) alone. Thus, faba bean as an intercrop in organic cabbage production systems improves land and N use efficiency by complementary root growth.